Dessecação de sementes de pitanga (Eugenia uniflora L.) - Alves, Michele Cerqueira da Silva (2018)
Brazilian cherry (Eugenia uniflora L.) seeds are sensitive to dehydration, difficulting their storage. The most usual procedure to determine seed viability is the germination test which is a destructive method. Fast and non-destructive analytical techniques, such as near-infrared spectroscopy (NIR), has been used in studies to estimate some properties of biological materials. Thus, the present study aimed to evaluate possible damages caused on Brazilian cherry seeds when subjected to dehydration and to explore the use of the NIR technique in the assessment of seed viability. Seeds were subjected to dehydration in silica gel (fast drying) and sodium chloride (slow drying) until reaching different moisture contents. The NIR spectra were obtained by optical fiber method using individualized seeds submitted or not to silica gel dehydration. The NIR data were analyzed by principal component analysis (PCA), and seed viability was determined by partial least squares discriminant analysis (PLS-DA). The initial moisture content of the seeds reduced from 60.4% to 15.6% in 25 days at fast drying, while in the slow drying process, it took 79 days. Viability was affected by moisture content but not by drying speed. PCA was able to clearly distinguish groups of seeds with and without drying. It was not possible to validate a model to classify the viability of the seeds using the PLS-DA. In the electrical conductivity test, the maximum value was 27.9 μS.cm -1 .g -1 for newly collected seeds. When seeds were subjected to dehydration, the values decreased, reaching 15.0 μS.cm -1 .g -1 for fast-dried seeds and 1.9 μS.cm -1 .g -1 for slow-dried seeds, both with 15% moisture content. Starch degradation was observed when seeds reached moisture content below 28%, while DNA integrity was maintained throughout dehydration. The results of this study showed that the dehydration of the seeds was detrimental to their viability. Furthermore, the presence of the seed coat after dehydration may have influenced the information collected for generating NIR spectra, as well as the electrical conductivity and germination test results. Thus, it is necessary more detailed studies on the relationship between dehydration and the presence of seed coat in Brazilian cherry seeds.